Handbook of research on modern cryptographic solutions for computer and cyber security - Gupta, Brij; Agrawal, Dharma P.; Yamaguchi, Shingo (Advances in information security, privacy, and ethics (AISPE), 2016)
This book identifies emergent research and techniques being utilized in the field of cryptology and cyber threat prevention, featuring theoretical perspectives, best practices, and future research directions.